Improving Weather Forecasts in West Africa Using WRF Model - Seidou Sanda, Ibrah; Laourou, Diane M.; Gadedjisso-Tossou, Agossou; Houngnibo, Mandela C. M.; Ali, Abdou (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Enhancing the quality of weather forecasts in Africa is crucial for mitigating the risks associated with potential life and property losses. Accurate impact assessment and informed decision-making depend on locally produced weather forecasts and tailored products from global and regional climate centers, such as AGRHYMET Regional Center. The Weather Research and Forecasting Model (WRF), a widely utilized model globally, has demonstrated its effectiveness in providing weather forecasts. AGRHYMET has set up a WRF model specifically tailored for weather forecasts over West Africa and the Sahel region. This info note presents preliminary outputs from this model, reflecting ongoing testing efforts. To maximize the effectiveness of the WRF model in the region, ongoing efforts are needed to conduct further investigations and enhance the capacity of the model used by AGRHYMET. Continued research and development will contribute to refining the accuracy and reliability of weather forecasts for West Africa and the Sahel region.